2016
DOI: 10.3928/01913913-20150929-18
|View full text |Cite
|
Sign up to set email alerts
|

Episodic Excessive Blinking in Children

Abstract: Episodes of excessive blinking rarely indicate neurologic disorders and frequently resolve spontaneously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…To date, studies have shown that excessive blinking in children is rarely an indication of a neurological disorder and usually resolves over time without intervention [ 25 ]. However, in clinical practice, the number of children with abnormal blinking as the main complaint is increasing, and the clinical symptoms are often reported as frequent or forced blinking.…”
Section: Discussionmentioning
confidence: 99%
“…To date, studies have shown that excessive blinking in children is rarely an indication of a neurological disorder and usually resolves over time without intervention [ 25 ]. However, in clinical practice, the number of children with abnormal blinking as the main complaint is increasing, and the clinical symptoms are often reported as frequent or forced blinking.…”
Section: Discussionmentioning
confidence: 99%
“…In children, excessive blinking is most frequently a functional and even transient disease, and it resolves spontaneously ( 3 ). However, excessive blinking, photosensitivity and blepharospasms may be the first clinical manifestation of a relevant disease, such as ophthalmic or neurological disorders.…”
Section: Introductionmentioning
confidence: 99%